Ultrathin Membranes for Separations: A New Era Driven by Advanced Nanotechnology - Zhang, Shiyu; Shen, Liang; Deng, Hao; Liu, Qinze; You, Xinda; Yuan, Jinqiu; Jiang, Zhongyi; Zhang, Sui (Advanced materials (Weinheim), 2022)
Ultrathin membranes are at the forefront of membrane research, offering great opportunities in revolutionizing separations with ultrafast transport. Driven by advanced nanomaterials and manufacturing technology, tremendous progresses are made over the last 15 years in the fabrications and applications of sub‐50 nm membranes. Here, an overview of state‐of‐the‐art ultrathin membranes is first introduced, followed by a summary of the fabrication techniques with an emphasis on how to realize such extremely low thickness. Then, different types of ultrathin membranes, categorized based on their structures, that is, network, laminar, or framework structures, are discussed with a focus on the interplays among structure, fabrication methods, and separation performances. Recent research and development trends are highlighted. Meanwhile, the performances and applications of current ultrathin membranes for representative separations (gas separation and liquid separation) are thoroughly analyzed and compared. Last, the challenges in material design, structure construction, and coordination are given, in order to fully realize the potential of ultrathin membranes and facilitate the translation from scientific achievements to industrial productions. Ultrathin membranes have undergone rapid development for fast and precise separations in the past 15 years. Here, a review is given on the assembly, structure, materials, and transport of sub‐50 nm membranes, with a focus on their fabrication‐structure‐transport relationships. Applications for liquid and gas separations are analyzed and compared to provide insights for future advances in high‐performance membranes.